The Effectiveness of Moringa Oleifera Lam Extract as an Oral Antimicrobial: a Systematic Literature Review - Indrastiti, Ratna Kumala; Rahmayanti, Febrina; Wimardhani, Yuniardini Septorini (Odonto : Dental Journal, 2024)
Background: The use of mouthwash to maintain oral hygiene has been carried out for many years. However, long-term use of mouthwash can cause side effects such as tooth discoloration, burning sensation and the death of normal oral flora. The use of herbal plant, such as Moringa oleifera lam has been studied as an alternative medicine because of its pharmacological properties and it is hoped to have minimum side effect. In this systematic literature review, we included the studies that have been investigate the antimicrobial capacity of Moringa oleifera lam as a basic knowledge to develop a preparation for oral hygiene maintenance.Method: A comprehensive literature search was performed utilizing four different electronic databases: PubMed, Scopus, Cochrane library, and EBSCO. Articles included in this study were published from 2013 to September 2023, with broad search criteria comprising MeSH-terms and free-text keywords Moringa Oleifera, Oral Antimicrobial, and Mouthwash.Result: At the beginning our search resulted in 17 articles, with 14 articles remaining after removal of duplication. We exclude five studies that do not meet the PICO criteria, resulting seven articles which included to this study.Conclusion: According to the literature review that has been carried out, Moringa oleifera lam has antimicrobial capacity which allows it to be used as a material in medicinal preparations. Further research, both in vitro and clinical research, will determine the effectiveness of Moringa oleifera lam in suppressing microorganisms.